New Interfaces in the Automated Landscapes of Logistics - Jesse LeCavalier (Footprint)
Metaphors of flows are often used to describe aspects of logistics, thereby suggesting smooth and inevitable operations while also obscuring the frictions and contingencies that characterize the industry. This article explores the consequences and possibilities of these modes by first elaborating some aspects of logistical operations in order to connect them to the contemporary built environment. It looks at the architectural components of the company Walmart in order to present hypothetical scenarios related to the future of the logistical landscape. By connecting these visual experiments to questions of representation, automation, and systems thinking, the article explores the ways we might challenge and extend the possibilities of logistics.